The Role of Teachers in Introducing Digital Literacy to Early Childhood at Ba Aisyiyah Mojosari Polokarto - Maryani, Sri; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to find out the role of teachers in introducing digital literacy to preschool children in Bustanul Athfal (BA) Aisyiyah Mojosari. The rapid development of digital technology requires teachers to instill digital skills from an early age. Methodology: This research is a qualitative research with a descriptive methodology and phenomenology research design. Data sources come from observations, in-terviews and documents. Results: The results of this study show the role of teachers in introducing digital lan-guage at a young age at BA Aisyiyah Mojosari, namely as facilitators, trainers, trainers and promoters so that children can develop skills in using digital technology from an early age and do digital work well. Applications/Originality/Value: To provide a safe and effective learning experience and develop digital skills and can increase children's interest in learning. Teachers act as guardians to ensure that children use digital media appropriately and responsibly to re-duce risks that may arise due to improper use of digital media, especially when accessing the internet.